Buruh Tani Jemputan Dalam Kehidupan Masyarakat Desa Sako Dua Kecamatan Kayu Aro Barat Kabupaten Kerinci Jambi - Wijaya, Wibi - (Pendidikan Sosiologi, 2014)
Peasant pickup in community Sako Dua village who work to elleviate familyâs economicdaily needs which is mostly dominated by women. Peasant pick up are peasant who do not workeveryday but they are such kind of workers which is need to be called or picked up first forworking. The purpose of this research is to see the factors causing the increase number of peasantpickup in community Sako Dua village West Kayu Aro district Kerinci Jambi.The theories which are used in this research is the theory from Tallcot Parsons, it is suchkind of Structural fungsionalism theory. This research used qualitative approach with descriptivetype. The informant of this research are peasant pickup and the owner of the field. In choosing theinformant of this research, the researcher uses purposive sampling technique with totall informantare 16 people. Kinds of data which is used is primer and sekunder data. The process of datacollection were done in two steps, they are (1) Observation (non-participant), (2) Deep interview.Unit data analysis is individual-Peasant pickup. In analyzing the data of this research, theresearcher used interactive analysis model which is consist of three steps. They are, (1) Datareduction, (2) Data description, (3) verification/ interpretation.Based on the result of the research it can be conclude that the factors causing the increasenumber of peasant pickup in community Sako Dua village is caused by internal factors andexternal factor from the peasant pickup themselves. Internal factors from peasant pickup such as1). Economic Condition, 2). PTPN 6 Kayu Aro Retire influence, 3). Do not have agricultural land,4). Do not have capital for cultivation, 5). Limited Job opportunity in the village. External factorsfrom peasant pickup such as 1). The occurance of Patron-klien relationship in society of Sako Duavillage with the owner of fields, 2). Less of power in managing the land.